Integrating digital recruitment and employer branding into strategic HRM to foster employee retention through perceived organizational support - Husainah, Nazifah; Suhartini, Suhartini; Fachrial, Peppy; Sopyan, Ahmad; Sundari, Pipit (Goodwood Publishing, 2025)
Purpose: This study examines how Digital Recruitment and Employer Branding influence Employee Retention through Perceived Organizational Support (POS), addressing gaps in strategic HRM research regarding the integrated role of digital hiring and employer branding. Research Methodology: A cross-sectional survey involving 200 employees from digitally mature Indonesian organizations was analyzed using PLS-SEM with 5,000 bootstrapped subsamples. The measurement model showed strong reliability and validity (? > .86; CR > .88; AVE > .54), and structural testing evaluated five direct hypotheses and mediation effects. Results: Employer Branding significantly predicts POS and retention, whereas Digital Recruitment enhances POS but shows no direct effect on retention. POS strongly predicts retention and fully mediates the Digital Recruitment–Retention relationship while partially mediating the Employer Branding–Retention link. The structural model explains 43% of POS variance and 51% of retention, supported by medium–large effect sizes and positive Q² values. Conclusions: The findings confirm POS as the key psychological mechanism through which modern HR practices translate into retention outcomes. Employer Branding drives retention both directly and indirectly, while Digital Recruitment contributes indirectly via POS. Limitations: Cross-sectional data limit causal inference, and the digital-sector sample restricts generalizability. Contribution: The study integrates digital recruitment and employer branding within one strategic HRM framework and establishes Digital Recruitment as an empirical antecedent of POS, reinforcing POS’s centrality in digital-era retention strategies.